Radiological and osteological study of the pelvic limbs in free‐ranging capybaras (Hydrochoerus hydrochaeris). (1st March 2018) - Brombini, G. C.; Rahal, S. C.; Schimming, B. C.; Santos, I. F. C.; Tsunemi, M. H.; Mamprim, M. J.; Alves, L. S.; Filadelpho, A. L.; Teixeira, C. R.
Summary: This study aimed to describe the radiographic anatomy and osteology and to evaluate angular radiographic measurements—Norberg angle, inclination angle and anteversion angle—of the pelvic limbs in free‐ranging capybaras. Twenty cadavers of free‐ranging capybaras ( Hydrochoerus hydrochaeris ), including five adults and 15 subadults, were studied. Ventrodorsal, craniocaudal, dorsoplantar and mediolateral radiographic views of the pelvic limbs were obtained. The radiographic features were described together with bone samples. The hip bone (os coxae), shaped like an isosceles trapezoid, was elongated and narrow with the presence of an oblong obturator foramen, sagittal ilial wing and rectilinear ilial body. The femoral shaft was relatively straight, while the greater trochanter was projected above the femoral head. No sesamoid bones of the gastrocnemius and popliteus muscles were observed radiographically or for those animals used in gross macroscopy. The fibula was located lateral and parallel to the tibia. Eight tarsal bones, four metatarsal bones and three digits were identified. The mean radiographic measurements included Norberg angle of 125.9°; respective angles of femoral inclination by the Hauptman B and Tomlinson methods of 139.9 and 141°; anteversion angle of the femoral head and neck of 29.80°. The bones of the pelvic limbs in capybaras have several anatomical characters and radiological features that are shared with members of the caviomorph superfamily Cavioidea. The radiographic angles measured in this study help characterize the functional morphology of this species.